Evidence in Civil Law - Slovenia - Ivanc, Tjaša (Law & Society, 2015)
Under the Article 22 of the Slovenian Constitution the right to equal protection of rights guarantees the right to state the facts and submit evidence, the right to be present at the taking of evidence and to be informed on the results of the taking of evidence. The principle of free assessment is a fundamental principle in Slovenian civil procedure included in Article 8 of the CPA. In the system of free assessment the judge is the one to evaluate the evidence without being bound by any formal rules on probative value of certain evidence. Probative value depends only on individual belief or conviction of the trial judge in each matter separately. The free assessment of evidence is the right and duty of the court to assess each piece of evidence separately and collectively. In the evidence-taking stage the CPA includes the special rules for each type of evidence, meant as a minimum guarantee for the right free assessment of the taken evidence and the free assessment of evidence presupposes that the evidence were taken by this rules. Even though, court decides which evidence will be produced for determination of the ultimate facts, the court is bound by the parties' right to propose evidence - with their procedural burden of proof. If the court rejects the proposal of a certain piece of evidence this rejections must be explained. In the following book the author discusses the key principles of the law of evidence in Slovenian civil procedure. The book provides analysis of the law of evidence, while placing the subject within its theoretical context. The subject is presented in a logical structure following on from the introduction of the basic principles through the rules for burden of proof, types of evidence, costs of evidence, the question of unlawful evidence, and the cross-border taking of evidence.